Criptógamos do Parque Estadual das Fontes do Ipiranga, São Paulo, SP. Algae, 44: Bacillariophyceae (Surirellales: Epithemia) - Morais, Krysna Stephanny De; Oliveira, Simone Alves De; Lehmkuhl, Elton Augusto; Silva-lehmkuhl, Angela Maria Da; Bicudo, Carlos Eduardo De Mattos (Instituto de Botânica, 2019)
ABSTRACT A survey of Epithemia (Bacillariophyceae) was carried out in the Parque Estadual das Fontes do Ipiranga (PEFI), São Paulo, SP, Brazil, in order to know the taxonomic diversity and the morphological variability of the genus. A total of 31 diatoms slides were analyzed of which five were used in this study. Five species were identified: E. proboscidea Kützing, E. gibba (Ehrenberg) Kützing, E. gibberula (Ehrenberg) Kützing, E. operculata (C. Agardh) Ruck & Nakov and Epithemia sp., with the dominance of periphytic species. One taxon was recorded for the first time in Brazil (E. proboscidea Kützing) and two taxa in the PEFI area (E. gibba (Ehrenberg) Kützing and E. operculata (C. Agardh) Ruck & Nakov).

RESUMO Foi realizado um levantamento florístico de Epithemia (Bacillariophyceae) na área do Parque Estadual das Fontes do Ipiranga (PEFI), São Paulo, SP, Brasil, com o objetivo de conhecer a diversidade taxonômica e a variabilidade morfológica do gênero. Ao total, 31 lâminas de diatomáceas foram examinadas das quais cinco foram usadas no presente estudo. Cinco espécies foram identificadas: E. proboscidea Kützing, E. gibba (Ehrenberg) Kützing, E. gibberula (Ehrenberg) Kützing, E. operculata (C. Agardh) Ruck & Nakov e Epithemia sp., com dominância de espécies perifíticas. Um táxon foi registrado pela primeira vez para o Brasil (E. proboscidea Kützing) e dois táxons para a área do PEFI (E. gibba (Ehrenberg) Kützing e E. operculata (C. Agardh) Ruck & Nakov).
Cryptogams of the Parque Estadual das Fontes do Ipiranga, São Paulo, SP. Algae, 44: Bacillariophyceae (Surirellales: Epithemia)
Keywords: diatom; floristic survey; periphyton; diatomáceas; levantamento florístico; perifíton